The Merits of Multicultural Literature: Exploring the inherent values of Multicultural Literature and the need for its inclusion in children’s early reading books - Jonsson, Letetia B., 1962- (2011)
Iceland is gradually changing from a homogenous Nordic society to a multicultural state, as evident in official demographic data and most noticeable in recent decades. These changes reflect an increasingly culturally diverse state, as the first government policy on the integration of immigrants confirms the reality of foreign citizens in Iceland. As a consequence of demographic changes, compulsory schools are becoming increasingly diverse and the need to develop all students’ knowledge of cultural diversity is through the use of multicultural literature. Teachers’ levels of awareness of the importance of using multicultural literature to reflect the schools’ changing environment are also necessary. An objective of this study was to establish the merits of multicultural literature, by exploring the inherent values of the concept, and why this genre of literature should be included in children’s early reading books. Another objective of this study was to examine teachers’ awareness of multicultural literature. This research involved both a literature review and qualitative inquiry. Central to this study were reader-response theories that affirm the value of multicultural literature. Second and equally important was the field work, involving a survey of teachers, using a semi-structured interview guide. Five schools in the city of Reykjavik agreed to take part in the study and nine teachers, acting as participants, were interviewed. The results support the argument for the inclusion of multicultural literature in children’s early reading books. Findings reveal low levels of awareness of multicultural children’s literature among teachers. A chronic lack of multicultural children’s books was evident across participating schools.